Robot Intelligence An Advanced Knowledge Processing Approach - Liu, Honghai.; Liu, Honghai.; Gu, Dongbing.; Gu, Dongbing.; Howlett, Robert J.; Howlett, Robert J.; Liu, Yonghuai.; Liu, Yonghuai. (Advanced Information and Knowledge Processing,, 2010)
Robot Intelligence is an exciting interdisciplinary field including engineering, information technology, machine learning, biological science and psychology. Its dramatic growth in practical applications is driven by both real-world requirements and maturity of related disciplines such as intelligent algorithms. It is expected that perception, understanding and reasoning capabilities play a crucial role in robot-assisted tasks and enable robots to exhibit similar performance on executing various tasks in both constrained and unconstrained environments. Robot Intelligence is a rare collection of chapters reflecting recent robotics developments from the advanced knowledge processing perspective. It also provides a comprehensive introduction and methodology to selected robotics topics including human robot interaction, human motion analysis, robot vision and advanced control. The robot intelligence methods presented enable readers to address many complex problems involving a wide range of robot sensors for the perception and understanding of the environment and the reasoning of the subsequent actions. The book’s comprehensive coverage will prove invaluable to senior undergraduates, PhD students, researchers and practitioners.